A chaos based image encryption algorithm using Rubik’s cube and prime factorization process (CIERPF) - R. Vidhya; M. Brindha (Journal of King Saud University: Computer and Information Sciences)
A novel Rubik’s cube based pixel level scrambling and simple XOR based diffusion is proposed in this paper to safely transmit multimedia information (images) through an untrusted channel, such as adaptive image content (i.e., plain image related) based initial random value generation is introduced to achieve high plain image sensitivity in order to overcome plain image related attacks. From this random value, the initial vectors of Henon map is obtained and this is iterated to obtain the key sequences to be applied over the Rubik’s cube row and column confusion processes. Also, the same random seed is involved in the key generation process based on prime factorization to be applied in diffusion. For each and every encryption of different plain image, the random list is changed dynamically and it is shown that the CIERPF method is secure against differential attacks. The CIERPF method is checked against various simulations to illustrate the security level of the technique. From the simulations, it is shown that the proposed methodology has good key space, high key sensitivity, and uniform distribution of cipher image pixels. Also differential cryptanalysis is performed for the proposed cryptosystem to prove its effectiveness towards differential attacks.